Monetary Incentives in Speeded Perceptual Decision: Effects of Penalizing Errors Versus Slow Responses - Dambacher, Michael; Hübner, Ronald; Schlössser, Jan (Frontiers in Psychology, 2011)
The influence of monetary rewards on performance has been widely investigated among various disciplines. The results, however, are inconclusive because positive reward effects have been observed only under specific conditions. Yet, the exact nature and the contribution of mediating factors are largely unexplored. The present study examined influences of payoff schemes as one of these factors. In particular, we manipulated penalties for errors and slow responses in a speeded categorization task. The data show improved performance for monetary over symbolic rewards only for a payoff scheme comprising higher penalties for slow responses than for errors. Conversely, payoff schemes with stronger punishment for errors than for slow responses resulted in impaired performance for monetary rewards. The results suggest that an emphasis of speed is favorable for positive influences of monetary incentives, whereas an emphasis of accuracy under time pressure has the opposite effect.